Shedding of endogenous MHC class I‐related chain molecules A and B from different human tumor entities: Heterogeneous involvement of the "a disintegrin and metalloproteases" 10 and 17. Issue 7 (18th April 2013) - Chitadze, Guranda; Lettau, Marcus; Bhat, Jaydeep; Wesch, Daniela; Steinle, Alexander; Fürst, Daniel; Mytilineos, Joannis; Kalthoff, Holger; Janssen, Ottmar; Oberg, Hans‐Heinrich; Kabelitz, Dieter
Abstract : The interaction of the MHC class I‐related chain molecules A and B (MICA and MICB) with the corresponding natural killer group 2, member D (NKG2D) receptor triggers cytotoxic effector activity of natural killer cells and certain T‐cell subsets and provides a costimulatory signal for cytokine production. Thus, the presence of MICA/B on transformed cells contributes to tumor immunosurveillance. Consequently, the proteolytic cleavage of MICA/B is regarded as an important immune escape mechanism of various cancer cells. To investigate the molecular machinery responsible for the shedding of endogenous MICA/B, we analyzed different human tumor entities including mammary, pancreatic and prostate carcinomas. Flow cytometry and enzyme‐linked immunosorbent assay (ELISA) revealed that all tested tumor cells constitutively expressed MICA and MICB on the cell surface and also released NKG2D ligands into the supernatant. We demonstrate that the "a disintegrin and metalloproteases" (ADAMs) 10 and 17 are largely responsible for the generation of soluble MICA/B. Pharmacological inhibition of metalloproteases reduced the level of released MICA/B and increased cell surface expression. Studies using RNA interference not only revealed a prominent role of ADAM10 and ADAM17 in NKG2D ligand shedding but also a tumor cell‐specific role of ADAM10 and/or ADAM17 in shedding of MICA or MICB. Moreover, we report that in the prostate carcinoma cell line PC‐3, MICA was not shed at all but rather was secreted in exosomes. These data indicate that the release of NKG2D ligands from individual tumor entities is by far more complex than suggested in previously reported MICA/B transfection systems. Abstract : What's new? Various immune factors patrol for substances found on the surfaces of tumor cells, and because each patient has a unique antitumor immune response, harnessing this surveillance ability represents an attractive strategy for personalized medicine. This study shows, however, that at least for the NKG2D immunosurveillance system, developing personalized therapeutic strategies may be more difficult than initially thought. Tumor shedding of the NKG2D ligands MICA/B, which facilitate tumor immune evasion, was found to be differentially regulated by ADAM proteases 10 and 17, indicating that ligand shedding is tumor cell‐specific and regulated by a multitude of mechanisms.